Efektivitas Layanan Informasi dengan Teknik Role Playing untuk Meningkatkan Motivasi Belajar Siswa SMAN 2 Palembayan - Fagel Andeska; Dina Sukma (Lembaga Yasin AlSys, 2024)
Learning motivation is a very important factor in the learning process. High learning motivation can encourage students to undertake learning activities and will have an impact on student learning achievement. The study aims to look at the effectiveness of the implementation of information services with role-playing techniques to improve student learning motivation. This study uses a quantitative approach, with the kind of research Quasi Experiment project The Non Equivalent Control Group. As for the population in this study is the whole of students SMAN 2 Palembayan classes X and XI, sampling using purposive samplings, then sampled are classes XIF2 and XIF3. The technique used in the data collection is by spreading questionnaires in the form of motivational learning racket, further analysed using the comparison of the gain score table and the Mann U Whitney 2 Independent Sample Test. The results of this study show that the implementation of information services with role-playing techniques can improve student learning motivation.